On limit sets of contractive functions on p-adic field - Mukhamedov, Farrukh; Khakimov, Otabek (AIP, 2016)
In the present paper, we define unconventional limit set of contractive functions on the unit ball of the p-adic numbers. Main result of the present paper states that the unconventional limit set is compact. Our results will open new perspective to the theory of self-similarity in a non-Archimedean setting